Improving transparency in data access processes: Developing best practice standards and promoting system-wide change through a competitive funding call - Macaulay, Yemi; Bellavia , Ester; Brophy, Rachel; Coulter, Angela; Glampson, Ben; Gilbert, Bethany; Holcroft, Alan; Mayer, Erik; McNamara, Edel; O'Sullivan, Katherine; Quattroni, Paola; Seymour, David; et al. (International Journal of Population Data Science, 2025)
Introduction Transparency in the use of data for research benefits the public and researchers by fostering trust and enabling efficient data sharing. Public support for access to their data for research depends on robust data security, the absence of conflicting interests, and a clear demonstration of public benefit, all of which must be evident through transparent practices. A lack of clarity in data access processes can delay research, highlighting the need for clear and streamlined approval procedures. To maintain what is often referred to as a `social license to operate', organisations must meet and uphold societal expectations, with transparency being a key dimension of that responsibility. Objective To develop and foster adoption of a set of transparency standards for the data science community, supporting trustworthy and streamlined data use for health and socio-economic research and planning. Methods A multi-stakeholder deliberation was undertaken, informed by two reviews of existing data access procedures across participating organisations. Stakeholders included healthcare and research organisations, data custodians, regulators, industry representatives, academic experts, and members of the public. Results The review and deliberation identified missed opportunities to inform and involve the public in data access procedures, along with inconsistencies in data access processes and supporting materials across the organisations. In response, we developed the Transparency Standards, comprising 28 recommended actions grouped into four themes: provision of clear data access guidance; clear website navigation designed to meet the needs of public and research users; regular review and iterative improvement of processes; and reporting of data access outcomes and information security findings. A targeted funding call facilitated the adoption of standards in 19 organisations, resulting in reusable transparency materials and transferable knowledge to support wider implementation. Conclusion The Transparency Standards support data custodians in strengthening openness and accountability in data access processes, helping to build public trust while simplifying procedures for researchers. Their broad adoption demonstrates a shared commitment to the ethical use of data. However, varying levels of implementation point to the need for continued investment to sustain progress and respond to public and researcher expectations.